Search for lightest neutralino and stau pair production in light gravitino scenarios with stau NLSP - Abreu, P; Adam, W; Adye, T; Adzic, P; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1999)
Promptly decaying lightest neutralinos and long-lived staus are searched for in the context of light gravitino scenarios. It is assumed that the stau is the next to lightest supersymmetric particle (NLSP) and that the lightest neutralino is the next to NLSP (NNLSP). Data collected with the Delphi detector at centre-of-mass energies from 161 to 183 GeV are analysed. No evidence of the production of these particles is found. Hence, lower mass limits for both kinds of particles are set at 95% C.L.. The mass of gaugino-like neutralinos is found to be greater than 71.5GeV/c2. In the search for long-lived stau, masses less than 70.0 to 77.5GeV/c2 are excluded for gravitino masses from 10 to 150eV/c2. Combining this search with the searches for stable heavy leptons and minimal supersymmetric standard model staus a lower limit of 68.5GeV/c2 may be set for the stau mass independent of the mass of the gravitino.